(untitled) (Journal of Atomic and Molecular Sciences, 2021)
The study of the multiphoton ionization of methyl iodide has a long and storied history. Here, we revisit this topic and present spectra of each of the photoionization and photodissociation fragments (C^+, CH^+, CH_2^+, CH_3^+, CH_3I^+, and I^+) using a custom time-of-flight mass spectrometer and a tunable dye laser over the excitation range of 550-740 nm (2.2-1.67 eV). The choice of this wavelength range allows for excitation through the A state and resonant ionization through higher energy levels using 4+1, 5+1, or 6+1 photons for excitation and ionization. Although the various fragments yield very similar spectra, fewer fragment ions are observed with increasing wavelength.